2003
DOI: 10.1007/s005950300022
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Collagenase in the Treatment of Sacrococcygeal Pilonidal Sinus Disease

Abstract: We therefore recommend an excision, marsupialization, and dressing with bacterial collagenase, in cases with noncomplicated SPSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…8 Total excision and marsupialization may be an advisable option for the treatment of infected sinuses provided that there is no abscess formation. 9 For many years, the most appropriate and effective method for the treatment of chronic noninfective SPD has been a matter of debate. Because the complete removal of unhealthy sinus tissue has been commonly performed during this operation, controversy has largely focused on the closure techniques.…”
Section: Introductionmentioning
confidence: 99%
“…8 Total excision and marsupialization may be an advisable option for the treatment of infected sinuses provided that there is no abscess formation. 9 For many years, the most appropriate and effective method for the treatment of chronic noninfective SPD has been a matter of debate. Because the complete removal of unhealthy sinus tissue has been commonly performed during this operation, controversy has largely focused on the closure techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The expectations from an ideal treatment can be listed as simplicity and convenience, good postoperative patient comfort, low complication rate, early return-to-work time and low recurrence rate. 9 Although several medical and surgical methods exist, ranging from phenol application to complex advancement flaps, no optimal treatment method has been defined yet due to high complication and recurrence rates. 10,11 Recently, lateralization of the natal cleft has gained significance in surgical PSD treatment.…”
mentioning
confidence: 99%
“…An examination of the individual studies included in this adverse event analysis reported infrequent pruritus, rash, edema, erythema (one case in one study), burning sensation at wound site (similar frequency between groups in several studies), burn bed infection (in a single study, seven cases with collagenase vs one case in control group), herpes infection (one case in one study), mild bleeding (one case in one study) and cellulitis (several cases in several studies). However, the risk ratio of developing cellulitis was not found to be statistically significantly different between treatment groups on subgroup analysis by Patry et al [21][22][23][24][25][26][27][28][29][30], and a high risk of bias was noted by the Cochrane risk of bias tool among the majority of RCTs included. The systematic review and meta-analysis contained information from some, but not all, of the more recent studies in the literature as it was limited to RCTs, excluding cohort (prospective or retrospective) studies.…”
Section: Pharmacoepidemiology Of Cco Usementioning
confidence: 99%